Фрагмент из рыцарского романа «Парциваль» Вольфрама фон Эшенбаха в переводе Эллиса (Льва Кобылинского) [A Fragment of the Chivalric Novel _Parzival_ by Wolfram von Eschenbach in Ellis’ (Lev Kobylinsky’s) Translation] - Poljakov, Fedor (Slavica Revalensia, 2023)
This is the first publication of a previously unknown translation of over 200 lines from Parzival by Wolfram von Eschenbach, which survived in Ellis’ (Lev Kobylinsky) anthology Pevtsy Germanii (Singers of Germany). Ellis started to compile this anthology with the purpose of demonstrating the incompatibility of genuine German cultural and religious traditions with the ideology of the Third Reich. His selection of texts for the translation was largely prompted by his previous studies, which included Richard Wagner and Wagner’s sources, esoteric interpretations of the image of the Holy Grail, and the reception of monuments of the Western European Middle Ages.